Financial Ratio Analysis To Assess Financial Performance PT. Timah Tbk 2019–2023 - Sibarani, Romida Br; Crisna , Heriyati; Maysara , Renny (Journal of Management, Economic, and Accounting, 2025)
This study aims to analyze financial ratios to assess the financial performance of PT. Timah Tbk for the 2019-2023 period. The research method used is descriptive quantitative. This study analyzes the profitability, liquidity, solvency, and activity ratios of PT. Timah Tbk for the 2019-2023 period as the research sample. The author used secondary data sources, namely data collected from the financial statements of PT. Timah Tbk listed on the Indonesia Stock Exchange through the website www.idx.co.id for the 2019-2023 period. The results indicate that in terms of profitability ratios, the company's ROE ratio can be considered unfavorable, while its NPM ratio can be considered quite good. Liquidity ratios indicate that the current ratio is good and the quick ratio is not good. Meanwhile, the company's solvency ratios, the DER and DAR ratios, are considered unfavorable because the resulting ratios are still below the applicable standards. In terms of activity ratios, the TATO ratio and inventory turnover ratio for the 2019-2023 period can be considered unfavorable.